DARURAT & REALISASINYA - Husnul Khatimah; Syarifuddin Syarifuddin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2014)
Human life in an opportunity will be blasted in an emergency, given the behavior, culture, needs, and human interaction are always evolving over time. In our country, the government imposed a state of emergency which often includes 'martial law' and 'civil emergency'. In the medical world is also known term emergency, the emergency department. Even in the era of the old order (1954) never was a scholars conference in Cipanas who decided that the current President, Ir. Soekarno, and the status of the state apparatus wa li al-amr daru ri bi al-shawkah (emergency rule because his power). This decision also reinforced by the decision of the 20th NU congress in Surabaya in the same year that certify the results of the scholars conference decision. It is also known as an emergency that has to do with economic issues, social, and all sorts of walks of life issues relevant to the needs of human life in general.Â